Aspects Supporting Lecturers’ Scientific Publications as Educational Development in Universities - Dina Prasetyaningrum; Arnesya Ramadhani; Dini Novi Rohmah (Jurnal Maksipreneur, 2026)
Social Exchange Theory examines how people interact within a group or company. It focuses on how workers think and make decisions based on fair treatment and trust in their leaders. When workers feel their relationships are built on fairness and mutual respect, they are more likely to put in their best effort. The study shows the importance of examining how managers lead, how much work lecturers have, and how they are rewarded in higher education to help them publish more scientific work. The findings suggest that transformational leadership and rewards are significantly associated with lecturers' performance in scientific publications, indicating that higher levels of these factors correlate with improved performance. The workload variable shows a negative link between workload and lecturers' scientific publication performance. This means that as the workload increases, the quality or amount of scientific publications decreases because the workload is too heavy for their abilities. If rewards can support such a large workload under social exchange theory, lecturers' scientific publication performance will also increase.